Social Capital In Social Studies Through Zoning School System - Mutiani, Mutiani; Subiyakto, Bambang (International Journal Pedagogy of Social Studies, 2019)
Social capital is a form of a social obligation entered into life. For society, social capital is used as a benchmark role, authority, responsibility, reward systems, and other linkages. Social capital and its relation to Social Studies provides space for social cohesion between groups. This article aims to describe the social capital in the context of learning social studies in a school zoning system. Qualitative approach used in the study. The descriptive method is chosen to present research results. Data collected observations, interviews, and documentation. The interactive analysis model of Miles and Huberman have to outline and describe the data that is saturated. The results of the study described the concept of the social model as the order of the social norm. For members of the community social capital is ideal unity. Instructional practices Social Studies contains the values of life so that students become good citizens. As for the connection with the practice of zoning as a policy, provide space to enable equality among learners. The zoning system trying to integrate social and academic status differences that occur in schools with the cluster system.